Pengaruh Lokasi dan Kualitas Produk Terhadap Keputusan Pembelian (Survei Pada Konsumen Toko Santi Collection Cikatomas Tasikmalaya) - Sendi Muhamad Rizki; Suci Putri Lestari; Arif Arif (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the simultaneous and partial influence of location and purchase quality on clothing purchasing decisions at the Sati Collection Store. The method used in this study is a survey method with a quantitative approach. The population studied was 100 respondents. The data collected were primary and secondary data. Data analysis in this study used multiple linear regression analysis using SPSS version 26. The results showed that location and product quality simultaneously had a significant effect on purchasing decisions at the Santi Collection Cikatomas Store. Location partially had a significant effect on purchasing decisions at the Santi Collection Cikatomas Store. Product quality partially had a significant effect on purchasing decisions at the Santi Collection Cikatomas Store.